2015
DOI: 10.1111/jns.12143
|View full text |Cite
|
Sign up to set email alerts
|

Pathological, biochemical, and biophysical characteristics of the transthyretin variant Y114H (p.Y134H) explain its very mild clinical phenotype

Abstract: Transthyretin (TTR) is a homotetrameric protein that must misfold in order to form amyloid fibrils. Misfolding includes rate limiting tetramer dissociation, followed by fast tertiary structural changes of the monomer that enable aggregation. Hereditary ATTR amyloidosis is an autosomal dominant genetic disorder with systemic deposition of amyloid fibrils induced by TTR gene mutation. We identified a rare Y114H (p.Y134H) TTR variant in a Japanese patient presenting with late-onset, very mild clinical course. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…It was recently shown that imaging of TTR in tissue reveals differences in LCP and LCO spectra indicating differences in structure. The differences were attributed to a mutation Y114H comprising a significant proportion of the amyloid protein deposit . Amyloid fibril structures from microcrystals of TTR peptides downstream and upstream of this site suggest that a structural difference due to the Y114H mutation could induce a packing variation and thereby a new polymorph to explain these differences in probe fluorescence.…”
Section: Ttrmentioning
confidence: 99%
“…It was recently shown that imaging of TTR in tissue reveals differences in LCP and LCO spectra indicating differences in structure. The differences were attributed to a mutation Y114H comprising a significant proportion of the amyloid protein deposit . Amyloid fibril structures from microcrystals of TTR peptides downstream and upstream of this site suggest that a structural difference due to the Y114H mutation could induce a packing variation and thereby a new polymorph to explain these differences in probe fluorescence.…”
Section: Ttrmentioning
confidence: 99%
“…The TTR Y114C mutation results in rapidly progressive cerebral amyloid angiopa- (16). Patients with the TTR Y114H mutation showed slowly progressive amyloidosis with carpal tunnel syndrome (17). In contrast, the TTR Y114S mutation as described here mainly showed rapidly progressive cardiomyopathy.…”
Section: Discussionmentioning
confidence: 56%
“…To comprehensively analyze the characteristics of the ABE system in human embryos, we produced the A-to-G mutation in human cells and embryos using ABE7.10. Five genes, TTR , 15 ALDOB , 16 COL9A2 , 17 KCNJ11 , 18 and RPE65 , 19 which had been reported to have pathogenic A-to-G point mutations, were selected (Figure S1A). We first tested the editing of these genes with the ABE system in HEK293T cells.…”
Section: Resultsmentioning
confidence: 99%